rom.js/cfd.xyz: An open-source framework for generating and visualizing parametric CFD results - Peña-Monferrer, Carlos; Díaz-Marín, Carmen (arXiv.org, 2022)
We present in this technical note an open-source web framework for the generation and visualization of parametric OpenFOAM simulations from surrogate models. It consists of a JavaScript module (rom.js) and a web app (cfd.xyz) to explore fluid dynamics problems efficiently and easily for a wide range of parameters. rom.js is a JavaScript port of a set of open-source packages (Eigen, Splinter, VTK/C++ and ITHACA-FV) to solve the online stage of reduced-order models (ROM) generated by the ITHACA-FV tool. It can be executed outside a web browser within a backend JavaScript runtime environment, or in a given web solution. This methodology can also be extended to methods using machine learning. The rom.js module was used in cfd.xyz, an open-source web service to deliver a collection of interactive CFD cases in a parametric space. The framework includes some tutorials, showing the whole process from the generation of the surrogate model to the web browser. It also includes a standalone web tool for visualizing users' ROMs by directly dragging and dropping the output folder of the offline stage. Beyond the current proof of technology, this enables a collaborative effort for the implementation of OpenFOAM surrogate models in applications demanding real-time solutions such as digital twins and other digital transformation technologies.